Metodologi ilmu Kalam - Ibrahim Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 1982)
This brief and short writing named as ``The Methodology of the Kalam,'' is an effort to explain a problem of the existence and originality of the methodology of the Kalam. Firstly, I quoted some opinions and findings from the orientalists explaining the negative stands and facts on this problem. They showed that Mutakallims were influenced by many external elements such as Christianity, Judaism and Greek philosophy. Secondly, I collected another opinions and explanation from another orientalists and from Muslim scholars in the Kalam to argue the first trend. According to my brief study on this problem, I would like to support the trend that the early Mutakallims were not influenced by external influences especially in their methodology